The Relationship Between Husband Support And The Selection Of Impalant Contraceptives In The Bangun Jaya Health Centre Working Area In 2024 - Diana, Pela; Sari, Liya Lugita; Putri, Yesi (Journal Hygeia Public Health, 2024)
Long-term contraceptive methods such as IUDs, implants and sterilization. The World Health Organization in 2022 states that the global prevalence of contraceptive use with all methods is estimated at 65% and modern methods at 58.7% in married women (World Health Organization, 2023). The purpose of the study was to determine the relationship between husband support and the selection of Implant contraceptives in the working area of Bangun Jaya Health Center in 2024. This study used analytic research with a cross sectional design. The population in this study were Fertile Age Couples in the working area of Bangun Jaya Health Center from June-July 2024 as many as 876 people. Purposive sampling technique, namely sampling based on researcher judgment and in accordance with the inclusion and exclusion criteria. The sample used by mothers of childbearing age couples was 67 people. Chi-square test results show that the variable of husband's support with the selection of contraceptives obtained chi-square p-value 0.000 (α <0.05), so it can be concluded that the relationship of husband's support with the selection of Implant contraceptives in the working area of Bangun Jaya Health Center in 2024.It is recommended to increase knowledge about the need for husband's support in choosing contraceptives in order to maintain household harmony.